Lymphocyte-Activation Gene 3 (LAG3): the Next Immune Checkpoint Receptor - Ruffo, Elisa (Semin Immunol, 2019)
Immune checkpoint therapy has revolutionized cancer treatment by blocking inhibitory pathways in T cells that limits the an effective anti-tumor immune response. Therapeutics targeting CTLA-4 and PD1/PDL1 have progressed to first line therapy in multiple tumor types with some patients exhibiting tumor regression or remission. However, the majority of patients do not benefit from checkpoint therapy emphasizing the need for alternative therapeutic options. Lymphocyte Activation Gene 3 (LAG3) or CD223 is expressed on multiple cell types including CD4(+) and CD8(+) T cells, and T(regs), and is required for optimal T cell regulation and homeostasis. Persistent antigen-stimulation in cancer or chronic infection leads to chronic LAG3 expression, promoting T cell exhaustion. Targeting LAG3 along with PD1 facilitates T cell reinvigoration. A substantial amount of pre-clinical data and mechanistic analysis has led to LAG3 being the third checkpoint to be targeted in the clinic with nearly a dozen therapeutics under investigation. In this review, we will discuss the structure, function and role of LAG3 in murine and human models of disease, including autoimmune and inflammatory diseases, chronic viral and parasitic infections, and cancer, emphasizing new advances in the development of LAG3-targeting immunotherapies for cancer that are currently in clinical trials.